2004
DOI: 10.1002/path.1537
|View full text |Cite
|
Sign up to set email alerts
|

Site‐independent prognostic value of chromosome 9q loss in primary gastrointestinal stromal tumours

Abstract: Although the significance of tumour site for estimating malignant potential in gastrointestinal stromal tumours (GISTs) has recently been recognized, site-specific genetic patterns have not to date been defined. This study examined 52 c-kit-positive primary GISTs (with a mean follow-up of 42.3 months in 51 cases) from three different locations (35 gastric, 12 small intestinal, and five colorectal) using comparative genomic hybridization (CGH). In general, tumour site correlated with key prognostic factors, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
1
11

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 19 publications
8
39
1
11
Order By: Relevance
“…Previous studies using conventional CGH and/or array-based genomic profiling indicated that loss of chromosome 9, especially 9p, is a specific indicator of unfavorable outcomes in GISTs (16)(17)(18). We corroborated this association by using ultrahigh-resolution aCGH, showing a striking predilection of chromosome 9 deletions, mostly involving both arms, in high-risk GISTs (70%).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous studies using conventional CGH and/or array-based genomic profiling indicated that loss of chromosome 9, especially 9p, is a specific indicator of unfavorable outcomes in GISTs (16)(17)(18). We corroborated this association by using ultrahigh-resolution aCGH, showing a striking predilection of chromosome 9 deletions, mostly involving both arms, in high-risk GISTs (70%).…”
Section: Discussionsupporting
confidence: 73%
“…We corroborated this association by using ultrahigh-resolution aCGH, showing a striking predilection of chromosome 9 deletions, mostly involving both arms, in high-risk GISTs (70%). Compared with previous series (15)(16)(17)(18)(19), the higher prevalence of 9p losses in high-risk GISTs may be attributable to better resolution of the current aCGH platform in detecting subtle interstitial deletions. Specifically, GISTs with chromosome 9 losses almost all involved the probe sets within 9p21.3 where p16 INK4A , the leading TSG of CDKN2A/2B loci, was recurrently inactivated in aggressive GISTs by various mechanisms, including the most common homozygous deletion (20,38).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…10 Some of these studies have implicated the 9q32-33 region as the prevailing target for deletion, suggesting that this region harbors an important tumor suppressor gene for lymphoproliferative cancers. The same region is lost in several other types of human cancers 11 with particularly high frequencies reported for transitional cell carcinomas of the bladder. 12 Fine mapping analysis in bladder cancer led to the identification of a putative tumor suppressor gene at 9q33.1, which has been designated as DBC1 (deleted in bladder cancer 1).…”
mentioning
confidence: 90%
“…Cytogenetic studies have reported correlations between the acquisition of additional chromosomal changes and aggressive behaviour such as gains at 5p and 20q and losses at chromosomes 1p, 9q and 9p. Gains at 8q and 17q have been detected in metastatic GISTs far more frequently than in primary tumours (Breiner et al, 2000;Debiec-Rychter et al, 2001;Derre et al, 2001;Gunawan et al, 2004;Kim et al, 2000;Miettinen et al, 2002a;O'Leary et al, 1999). Therefore, these chromosomal aberrations appear to be secondary events and may play an important role in tumour progression (Heinrich et al, 2003a) ( Figure 5).…”
Section: Chromosomal Losses and Gainsmentioning
confidence: 99%